A Scale to Assess Activities of Daily Living in Pantothenate Kinase‐Associated Neurodegeneration. Issue 2 (22nd January 2019) - Marshall, Randall D.; Collins, Abigail; Escolar, Maria L.; Jinnah, H.A.; Klopstock, Thomas; Kruer, Michael C.; Videnovic, Aleksandar; Robichaux‐Viehoever, Amy; Swett, Laura; Revicki, Dennis A.; Bender, Randall H.; Lenderking, William R.
ABSTRACT: Objective: Pantothenate kinase‐associated neurodegeneration (PKAN) is an autosomal‐recessive, neurodegenerative disorder with a mixed‐motor phenotype caused by a defective PanK2 enzyme, for which there are few adequate treatment options. Clinimetrically sound measures of patient‐reported outcomes are necessary to facilitate therapeutic development for this debilitating disease. This study's objective was to develop such a scale and assess its clinimetric properties. Methods: A conceptually driven, iterative, content development process incorporating input from experts, caregivers, and patients was used. Scale items were initially adapted from the Unified Parkinson's Disease Rating Scale (UPDRS) Part II resulting in the 12‐item Pantothenate Kinase‐Associated Neurodegeneration Activities of Daily Living (PKAN‐ADL). The PKAN‐ADL scale was administered to caregivers (n = 37) and patients (n = 2) twice over 2 weeks, along with selected Quality of Life in Neurological Disorders (Neuro‐QoL) measures, selected attributes of the Health Utilities Index (HUI)‐2/3, and the Stroke Aphasia Depression Questionnaire (SADQ‐10) to assess construct validity. Results: Internal consistency was 0.93, with excellent test‐retest reliability (intraclass correlation coefficient = 0.99). Of the 12 items, 25% (n = 3) showed a ceiling effect >30% (range, 31–54) and 42% (n = 5) showed a floor effect >30% (range, 31–46), reflecting disease heterogeneity. Convergent validity was shown with Neuro‐QoL measures ( r s > 0.90) and HUI‐2/3 attributes ( r s ≥ 0.48); divergent validity was demonstrated with the SADQ‐10 ( r = 0.11). Participants reported a high level of comprehension (98%), and average item relevance ratings (0–10 scale) ranged from 7.0 to 9.9. Conclusion: The PKAN‐ADL scale demonstrated acceptable content validity, with evidence of construct validity and excellent reliability. Overall results support the use of the PKAN‐ADL scale in clinical trials.